ESTUDIO DE LA DIROFILARIOSIS CANINA EN LA RIBERA DEL RÍO CHILLÓN, LIMA - Chipana Q., Carlos (2002)
The main objective of the study was to determine the presence of dirofilariosis (D. immitis) in districts of Lima located along the Chillon river (Puente Piedra, Comas, Carabayllo, Los Olivos and Ventanilla). Blood samples were collected in vacuotainer tubes containing anticoagulant from 200 dogs of 1-10 years of age that were selected at random, without distinction among breeds and sex. Samples were processed using three diagnostic tests: the method of microcapillary, Knott modified for microfilarias, and the ELISA test that detects antigens of secretion and excretion of the adult parasite. The overall results indicated 3.2 ± 2.4% of infection when using the enzymatic ELISA test, whereas 1.5 ± 1.7% when using the Knott modified and the mircocapillary tests. The prevalence of dirofilariosis in the monitored districts was: 4.4% in all three tests in Puente Piedra, 5% using the ELISA test in Ventanilla; 2.5% in all three tests in Comas, 2.5% using the ELISA test en Los Olivos; and 0% in Carabayllo. It was concluded that dog dirofilariosis does not represent a mayor parasitic problem; however preventive and control measures should not be left aside in order to keep the current level under control.